Stroke and COVID-19: An Umbrella Review: Stroke and COVID-19 - Shahsavarinia , Kavous; Hajipoor kashgsaray, Nasim; Ghojazadeh, Morteza; Falaki, Zahra; Soleimanpour, Maryam; Soleimanpour, Hassan (Archives of Academic Emergency Medicine, 2024)
Introduction: Acute ischemic stroke (AIS) and intracerebral hemorrhage (ICH) are among the acute cerebrovascular diseases (CVDs) that have been reported as a result of COVID-19. It will be a significant step forward if our research helps improve the compilation and analysis of existing data from other studies. Methods: The study is registered on PROSPERO with an ID of CRD42023464058. It encompasses articles published until December 2023 and involves searching databases such as PubMed, Scopus, Web of Knowledge, Embase, and Cochrane. Additionally, we conducted manual searches in respected publications within this discipline, utilized the Google Scholar search engine, and conducted reference checks, citation checks, and study of gray literature. The publications’ reporting quality was assessed using the "Assessment of Multiple Systematic Reviews" (AMSTAR) checklist. The meta-analysis was conducted using Stata software (StataCorp, version 16). Results: We analyzed the findings of 23 meta-analyses, which included 795 articles and encompassed 5,937 patients who had previously experienced a stroke. The average age of these patients was 62.3 years, and 68.3% were male. The findings indicated that the collective incidence of stroke among individuals with COVID-19 is roughly 1.75% [95% confidence interval (CI): 0.4%-3.03], with 1.59% for ischemic strokes and 0.3% for hemorrhagic strokes. 32.3% (95% CI: 27.8%-36.9%) of COVID-19 patients with stroke passed away, approximately 27% were discharged from the hospital with very mild or no complications, and around 28.1% (95% CI: 14.1%-42.1%) were referred for rehabilitation. Conclusions: The overall rate of stroke in COVID-19 patients was approximately 1.75%, with a higher incidence in males and those with an average age of 62.3 years. Almost 80% of the strokes were ischemic, and the mortality rate was approximately 32%. Finally, 27% of the patients were discharged without complications, and 28% required rehabilitation.